TINJAUAN STRATEGI VISUAL VIDEO KAMPANYE PROGRAM CAPRES PRABOWO VERSI MAKAN SIANG DAN SUSU GRATIS - Hasni, Fatimah Yasmin; Rahim, Aldrian Agusta; Hindraruminggar, Rika (INSIDE : Jurnal Desain Interior, 2025)
This study aims to analyze the visual strategy used in the campaign video of the Indonesian presidential candidate pair Prabowo Subianto and Gibran Rakabuming Raka, titled “Free Lunch and Milk”. The 30-second video features Prabowo as a child-like animated character delivering political messages through a light and friendly visual approach. The study employs a qualitative descriptive method using a single case study, analyzed through visual semiotics and message appeal theory. The findings indicate that the video combines rational and emotional appeals by utilizing a dominant light blue color palette, the “Gemoy” character design, and casual typography to create a warm and child-friendly candidate image. This research highlights the strategic role of visual communication design in shaping voter perception through accessible and structured visual elements. The study is expected to contribute to the development of political campaign design that is communicative, ethical, and relevant in today’s digital culture